The Role of Nickel Downstreaming in Advancing Green Economy Transformation and Foreign Direct Investment in Indonesia - M. Nashrullah; Frida Eka Ristanti; Resty Abdillah Paryanda; Restu Asa Marisza Sukma; Rokhmat Subagiyo; Muhammad Aswad (Economics and Digital Business Review, 2026)
This study analyzes the transformation of Foreign Direct Investment in the nickel downstream sector in Indonesia within the framework of a green economy. This research aims to fill the gap in the literature regarding the integration between downstream policies, foreign investment patterns, and environmental sustainability principles. Using a structured literature study approach with thematic analysis techniques, this study synthesizes secondary data from accredited journal articles, government reports, and related institution publications between 2015 and 2025. The results of the study show that downstream policies have succeeded in changing the character of FDI from resource extraction-oriented to value-added industry-based strategic investments, especially in the electric vehicle supply chain. However, this transformation faces an ecological paradox, where the nickel production process still relies on fossil energy. Therefore, the success of nickel downstream must be assessed based on the quality of green technology transfer and the application of Environmental, Social, and Governance (ESG) principles to ensure a truly sustainable modernization of the industry.